Unique functions for Notch4 in murine embryonic lymphangiogenesis - Ajit Muley; Minji Kim Uh; Glicella Salazar-De Simone; Bhairavi Swaminathan; Jennifer M. James; Aino Murtomaki; Seock Won Youn; Joseph D. McCarron; Chris Kitajewski; Maria Gnarra Buethe; Gloria Riitano; Yoh-suke Mukouyama; et al. (Angiogenesis, 2022)
In mice, embryonic dermal lymphatic development is well understood and used to study gene functions in lymphangiogenesis. Notch signaling is an evolutionarily conserved pathway that modulates cell fate decisions, which has been shown to both inhibit and promote dermal lymphangiogenesis. Here, we demonstrate distinct roles for Notch4 signaling versus canonical Notch signaling in embryonic dermal lymphangiogenesis. Actively growing embryonic dermal lymphatics expressed NOTCH1, NOTCH4, and DLL4 which correlated with Notch activity. In lymphatic endothelial cells (LECs), DLL4 activation of Notch induced a subset of Notch effectors and lymphatic genes, which were distinctly regulated by Notch1 and Notch4 activation. Treatment of LECs with VEGF-A or VEGF-C upregulated Dll4 transcripts and differentially and temporally regulated the expression of Notch1 and Hes / Hey genes. Mice nullizygous for Notch4 had an increase in the closure of the lymphangiogenic fronts which correlated with reduced vessel caliber in the maturing lymphatic plexus at E14.5 and reduced branching at E16.5. Activation of Notch4 suppressed LEC migration in a wounding assay significantly more than Notch1, suggesting a dominant role for Notch4 in regulating LEC migration. Unlike Notch4 nulls, inhibition of canonical Notch signaling by expressing a dominant negative form of MAML1 (DNMAML) in Prox1+ LECs led to increased lymphatic density consistent with an increase in LEC proliferation, described for the loss of LEC Notch1 . Moreover, loss of Notch4 did not affect LEC canonical Notch signaling. Thus, we propose that Notch4 signaling and canonical Notch signaling have distinct functions in the coordination of embryonic dermal lymphangiogenesis.